Research on pedagogical design strategies of children's furniture for children aged 3-6 - promotion effect of traditional cultural elements on children's cultural enlightenment in new Chinese-style desk design - Lin Li,; Siti Sarah Binti Herman,; Khairul Manami Kamarudin, (Environment and Social Psychology, 2025)
Traditional culture enlightenment plays an important role in preschool education. Children's furniture serves as a core element of daily living environments. Its design contains cultural and educational value. This study is based on environmental psychology and social learning theory. It takes New Chinese-style desks used by children aged 3-6 as the research object. The application strategies of traditional cultural elements and their effects on children's cultural enlightenment are systematically explored. This study adopts a mixed-method approach. Data were collected from 120 children and their parents. The methods include questionnaire surveys, behavioral observations, in-depth interviews, design practices, and quasi-experimental studies. The findings show several key results. First, the cognitive ability of children aged 3-6 toward traditional cultural elements increases significantly with age. The recognition rate rises from 52.3% to 86.5%. Second, the optimal effect is achieved when traditional elements account for 25-35% of the design, multiple sensory channels are activated, and 3-4 teaching functions are integrated. Third, the New Chinese-style desk improves children's cultural cognition by 69.6%. This is significantly higher than the control group's 27.0%. Fourth, social and psychological factors have key moderating effects. These factors include parental participation and family cultural atmosphere.This study proposes systematic design strategies at three levels: form, decoration, and function. A mechanism model is constructed as "physical environment - exploratory behavior - sensory experience - cultural cognition". The study provides theoretical basis and practical guidance for the pedagogical design of children's furniture and the innovative inheritance of traditional culture.